(untitled) (PlaySpace, 2023)
In this paper I will present a project for a ”play space” where I was asked to present a design for Stavanger Forum. This project is a good example of a self-organized and Template Algorithm design that triggers and attracts the Multiplicity design needed for a de-colonization. Update 14.12.2024: New file uploaded, with two new pictures and some ortographic corrections.